Fully aminated rigid-rod aramid reinforced high strength epoxy resin and its composite with carbon fibers. (12th April 2022) - Wang, Weitao; Yu, Boshi; Zhang, Yiwei; Peng, Mao
Abstract: Poly( p -aminophenylene aminoterephthalamide) ((NH2 )2 -PPTA), a new organo-soluble fully aminated rigid-rod aramid has been synthesized by the polycondensation of nitroterephthalic acid and 2-nitro-1, 4-phenylenediamine and then hydrogenation-reduction of the nitro side groups. (NH2 )2 -PPTA was then used as the modifier of epoxy resin (EP) and carbon fiber (CF)/EP composites and their mechanical properties were systematically investigated. Because all the benzene rings in (NH2 )2 -PPTA contain amino side groups, (NH2 )2 -PPTA has excellent solubility in organic solvents and EP. In addition, the amino side groups are able to react with the matrix so as to effectively integrate the rigid-rod (NH2 )2 -PPTA into the cross-linked molecular network of EP and facilitate the stress transfer between EP and (NH2 )2 -PPTA. The tensile and flexural properties and notch impact strength of EP are greatly increased with the addition of only 0.5 wt% (NH2 )2 -PPTA. Unusually high tensile strength and flexural strength have been achieved, which reach 140.6 ± 4.1 MPa and 237.9 ± 12.3 MPa, respectively. Moreover, addition of a small amount of (NH2 )2 -PPTA also significantly improves the flexural strength, toughness and the interlaminar shear strength of CF/EP composites. Compared with previously reported nanofillers and other rigid-rod polymers, (NH2 )2 -PPTA shows better reinforcing and toughening effect for EP and CF/EP composites owing to its great solubility, reactivity and inherent great mechanical properties. Graphical abstract: Image 1